Design and synthesis of biotinylated Hexylselen as a probe to identify KGA allosteric inhibitors by a convenient biomolecular interaction assay. Issue 17 (1st September 2019) - Hou, Wei; Fang, Jinzhang; Su, Lin; Ye, Hengyu; Ruan, Benfang Helen
Graphical abstract: Abstract: Hexylselen is a novel submicromolar dual KGA/GDH inhibitor, which demonstrates potent inhibition of cancer cells with minimal toxicity. To further investigation its mechanism of action, we designed and synthesized its biotinylated derivative2 as a novel probe. From commercially available starting material, 2 was obtained in 6 steps with 13.4% overall yield. It is notable that this practical synthetic route give a template for the preparation of unsymmetrical di-benzo[ d ][1, 2]selenazol-3(2 H )-ones. Based on probe2, we developed a novel biomolecular interaction assay for convenient and reliable test of KGA allosteric inhibitors and confirmed that hexylselen as an allosteric inhibitor of KGA sharing the same binding pocket with BPTES but not with Ebselen via competitive experiments.